Gender quotas influence the appointment of women to precarious leadership positions: A signalling approach - Meir Shemla; Anika Ihmels; Juergen Wegge (Journal of Occupational and Organizational Psychology, 2024)
In this research we address the ongoing debate about the existence of the glass-cliff phenomenon by investigating boundary conditions and mechanisms influencing its persistence and decline. Drawing on signalling theory, we hypothesize that the glass-cliff's presence fluctuates with the clarity of signals associated with appointing women board members at various stages of quota policy implementation. In Study 1, we analyzed a dataset of 258 board appointments in German-listed companies from 2003 to 2020. We found that women executives were more likely to be appointed following periods of declining performance during Stage 1 (pre-quota announcement) and Stage 3 (post-quota enforcement), but not in Stage 2 (post-announcement, pre-enforcement). In Study 2, an experiment with 476 respondents, we tested for changes in signal clarity as an underlying mechanism. Results indicate that signal clarity associated with appointing women following performance decline is influenced by quota policies. Signal clarity was highest during stages 1 and 3, but diminished in Stage 2. These findings support the signalling explanation for the glass-cliff, highlighting that its occurrence is influenced by country-level policies and emphasizing that the symbolic value of appointing women to board positions as indicators of change depends on the clarity of these signals.
Keywords: 650; glass cliff; leadership; quotas; signalling gender